Improving Students’ Interest and Learning Outcomes in Maharah Qira’ah through the TGT Model in Senior High School - Kholilurrohman, Muchammad; Moh. Ainin; Ach. Rifqiy Al Nabiil (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2026)
Abstract: This study aims to describe the implementation of the Teams Games Tournament (TGT) model in teaching maharah qira’ah and to enhance students’ interest and learning outcomes in maharah qira’ah through the application of the TGT model among high school students. This classroom action research was conducted in two cycles with the participants being students of class XI-E at SMA Islam Malang. Data were collected through observation, learning interest questionnaires, and achievement tests. The findings indicate that the TGT model was implemented in five stages: class presentation, team work, games, tournament, and team recognition. This approach fostered collaborative and competitive learning, helping students comprehend Arabic texts, both explicit and implicit. Students' interest in learning increased from an average of 73.8 in the pre-cycle to 82.7 in cycle I and 83.5 in cycle II, supported by innovative learning media such as question cards and the Arabic Monopoly game. Students' learning outcomes also showed significant improvement, from 88.5 in the pre-cycle to 91.6 in cycle I and 93.5 in cycle II. These findings suggest that the TGT model is not only effective in increasing students’ learning interest but also has a positive impact on their maharah qira’ah achievement. Keywords: TGT Model, Maharah Qira’ah, Learning Interest and Outcomes